"Bubble-in-nanorod" hierarchical hybrid fiber: A highly-efficient design for pyrophosphate-based freestanding cathodes towards fast sodium/lithium intercalation. (July 2018) - Deng, Chao; Zhang, Sen; Wang, Huifeng; Zhang, Guoming
Abstract: Tailoring electroactive materials into diverse functional architecture are triggering unprecedented innovations in the promotion of energy storage devices. Herein, we introduced a general strategy to prepare "bubble-in-nanorod" hierarchical hybrid fibers for fabrication of flexible pyrophosphate cathodes with superior lithium/sodium storage properties. The hollow spheres, which are composed of pyrophosphate nanoscale crystals and carbon matrix, are uniformly distributed within the porous carbon-based fiber. The prepared "bubble-in-nanorod" hierarchical structure not only can provide a bicontinuous conductive skeleton for fast electron transport, but also can effectively protect the crystal against structural deterioration, and thus is favorable to fast ion transport and stable structure integrity. Two kinds of pyrophosphates, i.e . Na3.12 Fe2.44 (P2 O7 )2 and Li2 FeP2 O7, are employed as examples in this study. For the first time, the mechanism on the combustion-assisted formation of the bubble-in-nanorod architecture is specified, and the effects of the functional structure on the ion intercalation chemistry of pyrophosphates are elaborated. Both pyrophosphate-based hybrid fibers can achieve better rate capability and longer cycling durability than the reference ones. Moreover, they are capable of long-term high-rate cycling. After six hundred cycles at alternate 20 and 3 C rates, the Na3.12 Fe2.44 (P2 O7 )2 and Li2 FeP2 O7 based fibers retain 94.4% and 95.1% of the initial capacity. Therefore, this work not only introduces a highly efficient architecture to realize the superior ion intercalation chemistry, but also provides a novel general strategy to fabricate high-performance flexible electrode for advanced lithium/sodium batteries. Graphical abstract: "Bubble-in-nanorod" hierarchical hybrid fiber is a highly efficient architecture to realize the superior performance for pyrophosphate, which provides a new clue to fabricate high-performance flexible electrodes for advanced lithium/sodium batteries.fx1 Highlights: "Bubble-in-nanorod" hierarchical fiber is a highly efficient structure for pyrophosphate cathodes. "Bubble-in-nanorod" structure has fast electron/ion transport pathways and provides effective protection to the crystal. The "combustion"-assisted formation mechanism is discovered to construct "bubble-in-nanorod" architecture.